PERAN STAIN SORONG TERHADAP PENGEMBANGAN KETERAMPILAN BAHASA INGGRIS DI PAPUA BARAT - Bunyamin Bunyamin (Pascasarjana IAIN Sorong, 2020)
A College has an important role in developing human resources. It has to arrange a good curriculum to answer the need of human in this live. A good curriculum will create a good learning and teaching. The skills are needed by students to face competitions in looking for jobs. English is one of skills which students need in the competition. State Islamic College of Sorong as one of Islamic College in West Papua gives a positive response to answer the students need in a local and global competition. It has three units in building English skills in West Papua. The first is Language Unit. It has done TOEFL Training and Test for students and society. This program develop three skills in English; Listening, Structure, and Reading. The second is Tarbiyah Faculty. It has conducted English Camp for Senior High School Students and University Students. This program improve students’ speaking skill. And the third is Bidik Misi. It has done a weekly meeting program. This program helps students to be more active in discussing a topic in English.